Implementasi Metode Human Resource Scorecad untuk Meningkatkan Kinerja Kerja Karyawan di PT Kinlaus Sukses Indoneisa (KS Group): jurnal spesia - ellgandireza selay; M. Dzikron; Agus Nana Supena (UNISBA Press, 2023)
Abstract. The growth of the food and beverage industry sector in Indonesia is increasing rapidly, especially in West Java because of the high population so that the KS Group Bandung company is required to meet the needs of the community, in supporting the needs of the community, adequate human resources are needed to support the success of the company's vision and mission, but the company has problems in the work performance of employees who do not support, resulting in a decrease in the quality of work owned by the company so that it hampers the company's vision and mission and optimization of performance such as increasing employee work delays, declining turnover, product complaints from consumers. Viewed from the aspect of the company's organization, the company is categorized as a medium industry based on the income and also the value of the company's investment. This research was conducted to design and measure the work performance of employees using the Human Resources Scorecard method. Human Resource Scorecard is a performance measurement system of Human Resources related to people, strategy and company performance in order to form a superior competitive company. The method applied to measure the extent of employee performance and is also useful for scientifically developing the company's human resources. There are four perspectives in measuring the Human Resource Scorecard, namely the financial, customer, internal business process and learn & growth perspectives. The stages of this research are the first to identify KPIs based on the company's business strategy, the second is to design an objective strategy to define the value creation process or the clarity of the organization's strategy to determine the steps for implementing the strategy. The third is to do indicator weighting, the weighting stage is done using expert choice software 11. Fourth, the scoring system is carried out using the higher is better, lower is better method. The five scoring system results obtained were categorized using the Traffic Light System method. The results of the study were 10 KPs divided into 2 financial KPIs, 3 customer KPIs, 2 internal bussiners process KPIs, and 3 Learning & Growth KPIs. From the results of the calculation of the weight score of the employee's performance in the company as a whole in each perspective, namely 60.7%, which means that the score obtained is the need for improvement and performance improvement. The results of the 10 KPO measurements obtained are divided into several categories, namely 2 KPIs in the red category, 6 in the yellow category, 2 in the red category. KPIs categorized as red indicate that the company's targets are still far from expectations, therefore the company must improve the KPIs and evaluate them in order to realize the company's vision and mission. The next research is to design employee performance using an assessment form, namely from a questionnaire, the second uses weighting with expert choice 11 and an employee performance appraisal data management form. Abstrak. Pertumbuhan sektor industri makanan dan minuman di Indonesia meningkat pesat khususnya di Jawa Barat karena populasi masyarakat yang tinggi sehingga perusahaan PT Kinlaus Sukses Indonesia dituntut memenuhi kebutuhan masyakarat, dalam menunjang kebutuhan masyarakat diperulukan Sumber Daya Manusia yang memadai guna mendukung keberhasilan visi dan misi perusahaan. Namum dalam hal ini perusahaan memiliki masalah didalam kinerja kerja karyawannya yang tidak mendukung, mengakibatkan turunnya kualitas kerja yang di miliki perusahaan sehingga memperhambat visi dan misi perusahaan dan optimalisasi kinerja seperti meningkatnya keterlambatan kerja karyawan, omset menurun, tingkat komplain produk dari konsumen. Dilihat dari aspek organisasi perusahaan, perusahaan dikategorikan industri menengah berdasarkan pendapatan dan juga nilai investasi perusahaan. Penelitan ini dilakukan untuk merancan dan juga mengukur kinerja kerja karyawan menggunakan metode Human Resources Scorecard. Human Resource Scorecard merupakan sistem pengukuran kinerja SDM yang berkaitan dengan orang, strategi serta kinerja perusahaan guna membentuk perusahaan berdaya saing yang unggul. Metode yang terapkan untuk mengukur sejauh mana kinerja karyawan serta juga berguna untuk mengembangkan sumber daya manusia yang dimiliki perusahaan secara ilmiah. Terdapat empat prespektif dalam pengukuran Human Resource Scorecard yaitu perspektif financial, customer, internal bussines process dan learn & growth. Tahapan penelitian ini pertama mengidentifikasi KPI berdasarkan strategis bisnis perusahaan, kedua merancang strategi objektif untuk mendefinisikan proses penciptaan nilai atau kejelasan strategi organisasi menetapkan langkah langkah untuk pelaksanaan strategi. Ketiga yaitu melakukan pembobotan Indikator, tahapan pembobotan dilakukan dengan menggunakan software expert choice 11. Keempat dilkukan scoring system dengan metode higher is better, lower is better. Kelima hasil scoring system yang diperoleh dilakukan pengkatagorian dengan menggunakan metode Traffic Light System. Hasil dari penelitian sebanyak 10 KPI terbagi 2 KPI financial, 3 KPI customer, 2 KPI Internal bussiners process, dan 3 KPI Learning & Growth. Dari hasil perhitungan bobot skor kinerja karyawan di perusahaan secara menyeluruh pada setiap presfektif yaitu 60,7% yang artinya skor tersebut perlunya perbaikan dan peningkatan kinerja. Hasil pengukuran 10 KPI yang diperoleh terbagi atas beberapa kategori, yaitu 2 KPI dalam kategori merah, 6 dalam kategori kuning, 2 dalam kategori merah. KPI yang berkategori merah menandakan target diperusahaan masih jauh dari harapan, oleh karena itu perusahaan harus memperbaiki KPI tersebut dan evaluasi guna mewujudkan visi dan misi perusahaan. Penelitan selanjutnya dengan merancang kinerja karyawan dengan menggunakan form penilaian yaitu from kueisioner, yang kedua menggunakan pembobotan dengan expert choice 11 dan form pengelolahan data penilaian kinerja karyawan.